The Trend of Using Social Media Technology for Business Actors for the Branding Process - Setiawan, Ariyono; Mubarok, Ahmad; Efendi, Efendi; Globalisasi, Safitri Era; Ika Marini, Ni Made (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
The development of social media has changed the business landscape, where businesses increasingly rely on this platform to develop brand identity and interact with consumers. The purpose of this study was to investigate trends in the use of social media technology in the branding process. This research stems from the importance of understanding how businesses are leveraging social media technology to achieve branding goals in an ever-changing environment. This study used online survey techniques to collect data from various industries and analyze it using descriptive statistical techniques. It was found that the most effective type of content for achieving branding goals was video, followed by images and graphics. Metrics like follower count, engagement rate, sales conversions, and website traffic are often used to measure the success of social media branding campaigns. In conclusion, social media technology plays a central role in branding success. Continuous adaptation and innovation are key to maximizing the potential of social media in achieving branding goals in an ever-evolving and changing business world.